A Corpus-based Contrastive Study on English and Chinese Semantic Prime happen and fasheng in Natural Semantic Metalanguage - Wang, Yajun (JOURNAL OF ADVANCES IN LINGUISTICS, 2021)
This paper reports a corpus-based study on English and Chinese semantic prime happen and fasheng in Natural Semantic Metalanguage. With the aids of computer software Wordsmith 5.0 and SPSS19.0, we conducted a contrastive study on happen and fasheng based on a small English and Chinese comparable corpus constructed by ourselves. By extracting evidence from the corpus, the distribution of happen and fasheng, their syntactic patterns, their colligation types as well as their semantic prosody are identified and analyzed. We found that there is no significant difference between English semantic prime happen and its Chinese counterpart fasheng with respect to their distribution, their syntactic patterns, their colligations, and their semantic prosody. The results reveal that semantic prime happen is identical with its Chinese counterpart fasheng. Thus it provides an evidence to justify the premise of the Natural Semantic Metalanguage Theory.